Protoplast Isolation and Culture of Dendrobium Sonia “Bom 17” - Yuphin Khentry,; Ampaiwan Paradornuvat,; Sureeya Tantiwiwat,; Salak Phansiri,; Niphone Thaveechai, (Agriculture and Natural Resources, 2006)
The optimization of Dendrobium Sonia “Bom 17” protoplast isolation and culture conditions were investigated. Protoplasts were successfully isolated from one-month-old leaves of in vitro-grown plantlets using an enzyme solution comprising 1% Cellulase Onozuka R-10, 0.2% Macerozyme, 0.3 M mannitol, 10 mM CaCl2.2H2O and 10 mM 2 (N-morpholino)-ethanesulfonic acid (MES) at pH 5.8. Approximately 3.97±0.63 × 105 protoplasts per gram fresh weight were obtained when digested in enzyme solution for 4 h on a shaker under dark conditions, then washed with 0.3 M mannitol solution supplemented with 10 mM CaCl2.2H2O and 10 mM MES, and purified with 0.3 M sucrose solution. Freshly isolated protoplasts were then cultured at final density of 2 × 105 protoplasts/ml in Kao & Michayluk medium (KM8P) by agarose-bead cultures under dark conditions at 25°C. First cell division was observed after culturing for 2 days and multicellular colonies (15-20 cells) were formed after 2 weeks.